2010
DOI: 10.2225/vol13-issue4-fulltext-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic characteristics of β-cyclodextrin production by cyclodextrin glycosyltransferase from newly isolated Bacillus sp. C26

Abstract: The kinetic characteristics of β-cyclodextrin production by a cyclodextrin glycosyltransferase (CGTase) produced by Bacillus sp. C26, a new isolate from a soil sample was investigated. Considering highest yield and initial production rate of β-cyclodextrin, among the starches examined, soluble starch, tapioca starch, sago starch, corn starch and rice starch, tapioca starch was the best substrate for this CGTase. The optimum temperature for tapioca starch gelatinization prior to its use as a substrate for β-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
12
0
3
Order By: Relevance
“…There are different approaches to enrich the yield of the target type of CD, including search for novel CGTase for this purpose, enzyme engineering of CGTase at central active site cleft (Takada et al 2003;Goh et al 2007) and, alternatively, modifying the substrates and enzymatic reaction conditions. Such parameters include starch source and concentration (Cheirsilp et al 2010), reaction pH (Hirano et al 2005), presence of certain additives and precipitants (Martins and Hatti-Kaul, 2003). In this study, we report the influences of different reaction parameters on the ratio and total yield of CDs produced by the action of CGTase from a newly isolated alkaliphilic Bacillus agaradhaerens KSU-A11 (Ibrahim et al 2010).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…There are different approaches to enrich the yield of the target type of CD, including search for novel CGTase for this purpose, enzyme engineering of CGTase at central active site cleft (Takada et al 2003;Goh et al 2007) and, alternatively, modifying the substrates and enzymatic reaction conditions. Such parameters include starch source and concentration (Cheirsilp et al 2010), reaction pH (Hirano et al 2005), presence of certain additives and precipitants (Martins and Hatti-Kaul, 2003). In this study, we report the influences of different reaction parameters on the ratio and total yield of CDs produced by the action of CGTase from a newly isolated alkaliphilic Bacillus agaradhaerens KSU-A11 (Ibrahim et al 2010).…”
Section: Introductionmentioning
confidence: 94%
“…G1 (Sian et al 2005) and from Bacillus sp. C26 (Cheirsilp et al 2010), while soluble starch was the best substrate for CGTase from Klebsiella pneumoniae AS-22 (Gawande and Patkar, 2001). This suggested that the various sources of starch could affect the CDs production, which is probably caused by the differences in the starch granules structure and properties (Sian et al 2005; Goh et al 2007).…”
Section: Effect Of Substrates On Cds Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) to provide cyclic a-(1!4)-linked glucooligosaccharides with six (a-CD), seven (b-CD), and eight glucose units (g-CD) (Rendleman 1999;Lichtenthaler 2010). This intramolecular transglycosylation is called cyclization reaction (Szejtli 1998;Cheirsilp et al 2010).…”
Section: Occurrence/sourcesmentioning
confidence: 99%